Strategi peningkatan kemampuan berbicara mahasiswa melalui pelatihan public speaking berbasis praktik dan umpan balik - Safitri, Citra Dwi; Sembiring, Surya Anantatama; Sudding, Muhammad Fahri Jaya; Musdalifah, Musdalifah; Kamariah, A. (Nur Science Institute, 2025)
Public speaking is a vital skill for students, particularly those majoring in English. However, many students still experience obstacles in terms of self-confidence and the courage to speak in public. This community service activity aims to improve public speaking skills through practice and feedback-based training. The training involved 25 students from various English study programs at Makassar State University with an experiential learning approach that included theory sessions, impromptu speech practice, and reflection. The evaluation results showed a significant increase in three main aspects: awareness of the importance of speaking skills, increased self-confidence, and courage to appear in public speaking. As many as 90% of participants stated that this training helped them be more prepared to speak in public. This activity shows that the practice and feedback approach is effective in building students' soft communication skills and is worthy of being integrated into self-development programs in higher education.